Use of aromatase inhibitors for height improvement in boys: a literature review (Research, Society and Development, 2023)
Introduction: Short stature is currently one of the most common reasons for seeking and referring patients to pediatric endocrinology. Such a demand occurs not only due to the physiological factors, but also the psychological ones involved. Objective: to analyze the specific literature on aromatase inhibitors and their use in children. Method: A narrative literature review was carried out using Pubmed, Google Scholar and UptoDate databases. For the search, the following descriptors were used: “aromatase inhibitor”, “children” and “growth”. Articles on the use of aromatase inhibitors in boys with short stature were selected. Articles that focused on the use of aromatase inhibitors in cancer, the use of aromatase inhibitors exclusively in McCune Albright Syndrome and that were not located in full were excluded. A total of 1028 scientific productions were found, of which 59 met the pre-established criteria. Results and Discussion: The aromatase enzyme is a cytochrome P450 enzyme and converts androgenic precursors into estrogenic precursors. Aromatase inhibitors delay growth cartilage senescence and may be indicated in boys with current short stature with psychosocial repercussions or inadequate prediction of final height. According to previously published studies, aromatase inhibitors have been shown to be effective in the treatment of short stature. It is concluded that aromatase inhibitor treatment effectively delays bone maturation and improves adult height.